Integrated sedimentology and ichnology of Late Jurassic fluvial point‐bars – facies architecture and colonization styles (Lourinhã Formation, Lusitanian Basin, western Portugal). Issue 2 (26th July 2017) - Gowland, Stuart; Taylor, Andrew M.; Martinius, Allard W.
Abstract: Integrated sedimentological and ichnological case studies of ancient meandering river systems have, for the most part, focused on the deposits of the fluvial–tidal transition zone; much less emphasis has been placed on the purely fluvial realm above the landward limit of tidal effects. This problem needs to be addressed so that in future the defining sedimentological and ichnological criteria assigned to ancient fluvial reaches are sufficiently well‐established to enable their separation from the down‐dip fluvial–tidal transition zone. Accordingly, a case study has been carried out on a well‐exposed meander belt deposit from the Late Jurassic Lourinhã Formation of the Lusitanian Basin, western Portugal (Praia Do Valmitão, Ribamar). Analysis indicates that the meander belt here comprised mixed‐load fluvial channels traversing a vegetated floodplain subject to a seasonal winter wet/summer dry palaeoclimate. This setting facilitated the development of both calcic palaeosols and shallow lakes on the adjacent floodplain. Critically, there is no evidence of the effects of tidal modulation on bedding structures, thereby establishing purely fluvial conditions. Heterolithic point‐bar deposits generated in this setting are bioturbated extensively by a trace fossil assemblage dominated by the meniscate trace Taenidium barretti, with Skolithos linearis, Planolites beverleyensis and Cylindricum isp. also recognized. A number of factors suggest that the Taenidium barretti producer in this case was a subaquatic organism living in an active fluvial channel setting (i.e. not colonizing subaerially exposed channel‐margin/floodplain deposits). Accordingly, there are some implications for current ichnofabric/ichnofacies models in the continental realm. Firstly, Taenidium ‐dominated ichnofabrics need not necessarily be confined to colonization beneath subaerially exposed surfaces; they might also be produced within submerged substrates. Secondly, there is scope to extend the range of the Scoyenia ichnofacies to include active fluvial channels and not simply those channels that were inactive or abandoned.